Creative Tourism Achievement in Thailand: Evaluated by Experts and Tourists - Wisudthiluck, Suddan; Saiphan, Pichet; Teparakul, Ornuma; Sindecharak, Teera (Thammasat Review, 2017)
This article intends to present the assessment criteria for evaluating 13 creative tourism activities in Thailand. The Faculty of Sociology and Anthropology, Thammasat University, and The Designated Areas for Sustainable Tourism Administration (DASTA), have jointly developed new destinations in tourism known as “Creative Tourism” in Thailand. Creative Tourism activities in Thailand consist of Muslim Cham’s way of life at Ban Nam Chiao, Coastal Fishery at Ban Bang Lamung, Sukhothai Classical Dancing Class, Sukhothai Celadon Workshop at Ban Koh Noi, Sukhothai Votive Tablet Workshop, Sukhothai Ceramic Workshop, Ceramic Forming and Painting Workshop, Sukhothai Motive: Art Workshop, Mothana Ceramic Workshop, Dan Sai Delicacies Cookery Class, Chiang Khan Cotton Quilt Workshop, Lanna Ceramonial Flags ‘Tung’ Workshop at Phra Kerd Temple and U-Thong Bead Making Workshop. Creative Tourism is a new tourism trend that provides tourists a chance to reciprocate and appreciate culture, social values and the environment through direct experience with the locals or activity’ owners (Wisudthiluck et al., 2011). The evaluation of 13 creative tourism activities was conducted from March to April 2015 by 5 experts and selected tourists interested in creative tourism after those activity’ owners attended the organized workshops, trainings, meetings as well as domestic and international study trips. Through the evaluation we have found that all the activities have enough potential and readiness to accommodate tourists in the future. The highest scoring activity was Sukhothai - Votive tablet Workshop followed by Lanna Ceremonial Flags ‘Tung’ Workshop at Phra Kerd temple and Dan Sai Delicacies Cookery Class with the score 92.83%, 90.73% and 89.35%. All 13 creative tourism activities meet the established evaluation criteria of area and process characteristics and other types of characteristics. Tourists were satisfied with creative tourism more than they had expected. The assessment criteria characteristics such as area, process, activities owner, management and environment characteristics indicate that tourists are highly satisfied with the activity. Tourists were especially satisfied with the activity owner characteristics, in which all the hosts were ready and willing to convey their specialties and knowledge to the tourist. Both our experts and tourists also reflected on how creative tourism can be beneficial for development. Hopefully, “Creative Tourism” as a new tourism trend that emphasizes the cultural value of a tourism area will help increase that areas economic potential.